2012
DOI: 10.5430/jha.v1n2p54
|View full text |Cite
|
Sign up to set email alerts
|

Medication Errors: Scope and prevention strategies

Abstract: Background: Medication errors are a significant public health concern. Although significant advances have been made, errors are still relatively common and represent an opportunity for healthcare improvement. Methodology/Principal findings:Since the publication of To Err is Human, medication errors have been under tremendous scrutiny. Organizations have moved towards a non-punitive approach to evaluating errors. This approach to medication errors has aided in identifying common pathways to medication errors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The most successful interventions are medication reviews conducted primarily by pharmacists with a multicomponent focus [2], even in the community practice setting [34]. This is very important in ensuring safer health services, as 1-10% of medication errors identified in patient care are associated with patient harm [4]. There are different scales in assessing causality in adverse drug reactions, such that when that is introduced in the curriculum, the students may be better positioned to identify the adverse drug reactions errors [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most successful interventions are medication reviews conducted primarily by pharmacists with a multicomponent focus [2], even in the community practice setting [34]. This is very important in ensuring safer health services, as 1-10% of medication errors identified in patient care are associated with patient harm [4]. There are different scales in assessing causality in adverse drug reactions, such that when that is introduced in the curriculum, the students may be better positioned to identify the adverse drug reactions errors [35].…”
Section: Discussionmentioning
confidence: 99%
“…Medication error is defined as "a failure in the treatment process that leads to harm to the patient" and it can occur at different stages in the provision of drugs to a patient [1][2][3][4][5][6]. Any health professional involved with drugs and patient care is vulnerable to make an error during the production, prescribing, transcribing, dispensing, and administration phase of a drug [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of sophisticated Health Information Technology (HIT) systems in our setting such as e-prescribing systems, CPOE, and bar-coded electronic Medication Administration Record has resulted in the majority of the error being at the level of drug administration,[ 19 20 21 ] and in our system, it is mostly the nursing staff who administer the drugs. It is said that nurses spend 40% of their time in medication administration.…”
Section: Discussionmentioning
confidence: 99%
“…Mahmood et al reported following environmental factors: lack of private space in the working area, the inappropriate design of the nursing unit, inadequate space in medication charting area, the small size of the medication room, using defective equipment for medical supplies, and inappropriate location of the nursing stations [26]. Also, Brunetti indicated that proper design of the work environment can prevent medication errors [27].…”
Section: Plain Language Summarymentioning
confidence: 99%